2012
DOI: 10.1200/jco.2011.37.2979
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Tailored Education Program for Disease-Free Cancer Survivors With Cancer-Related Fatigue: A Randomized Controlled Trial

Abstract: An Internet-based education program based on NCCN guidelines and TTM may help patients manage CRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
297
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(307 citation statements)
references
References 32 publications
6
297
2
2
Order By: Relevance
“…Future research should focus on delivery modalities that decrease burden and increase acceptability in a larger proportion of caregivers (e.g., those who are feeling too overwhelmed to attend in-person intervention sessions). Telephone interventions have been successful in providing efficacious psychosocial interventions for cancer patients and caregivers [36][37][38][39] and recent research on web-based interventions [40][41][42] and interventions using Smart phones and other delivery platforms [43] appear promising. These interventions provide more flexibility and cancer caregivers report they would reduce burden [44].…”
Section: Discussionmentioning
confidence: 98%
“…Future research should focus on delivery modalities that decrease burden and increase acceptability in a larger proportion of caregivers (e.g., those who are feeling too overwhelmed to attend in-person intervention sessions). Telephone interventions have been successful in providing efficacious psychosocial interventions for cancer patients and caregivers [36][37][38][39] and recent research on web-based interventions [40][41][42] and interventions using Smart phones and other delivery platforms [43] appear promising. These interventions provide more flexibility and cancer caregivers report they would reduce burden [44].…”
Section: Discussionmentioning
confidence: 98%
“…Interactive websites QoL Salzer [39] Yun [43], Osei [32] Lieberman [37] Osei [32] Owen [38], Ruland [51], van den Brink [33] …”
Section: Outcome Domain Email Online Education Intervention Osg/messamentioning
confidence: 99%
“…This review includes studies of patients with lung cancer [31], prostate cancer [32], head and neck cancer [33] and breast cancer [34][35][36][37][38][39][40], as well as mixed cancer populations [41][42][43][44].…”
Section: Cancer Populationmentioning
confidence: 99%
“…In this review we identified only one paper in the cancer field that met our eligibility criteria. Recently, however, positive results of a web-based intervention to reduce depression in cancer survivors [45], and of a webbased, tailored education program to reduce cancer-related fatigue and anxiety [46] have been reported. Several additional RCT's of web-based interventions for cancer patients are currently on-going (www.clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 99%
“…The 4 reviews included 46 unique IT services (described in 74 studies). The additional search and expert input yielded additional information on 5 patient portal services, 6 e-PRO services and 3 electronic survivorship care (plan) support systems [45][46][47][48][49][50][51][52][53][54][55] (see Appendix 2.2 for an overview). IT services could be divided into five categories: 1) educational services (including electronic survivorship care plan services); 2) patient-to-patient services;…”
Section: Cancer-specific Findingsmentioning
confidence: 99%